Business Implications of Integrated Product and Service Offerings - Lindahl, M.; Sakao, T.; Öhrwall Rönnbäck, A. (Cranfield University Press, 2009)
This paper explores the business implications of Integrated Product and Service Offerings (IPSOs). The objective is to show examples of the business implications of IPSOs from a supplier’s perspective, and to suggest specifications for supporting methods needed for such an industrial company. The paper is largely based on empirical case studies of 120 Swedish manufacturing companies of all sizes. Results from the case studies show that both small and large companies that conduct the transition towards IPSOs face several important strategic challenges, some of them associated with high risk.
Organised by: Cranfield University
Keywords: Product Service Systems (PSS); IPS²; methods; Integrated Product Service Engineering